The Validity of the Turkish Translation of Mania Rating Scale, and the Depression Rating Scale for Children and Adolescents - Mustafa Tunçtürk; Çağatay Ermiş; Serkan Turan; Dicle Büyüktaşkın; Yesim Sağlam; Mutlu Özbek; Sezen Alarslan; Denizhan Tanyolaç; Celal Yeşilkaya; Ayse Sena Yuksel; Omca Güney; Dilara Akça; et al. (Van Tıp Dergisi, 2023)
INTRODUCTION: The aim of this study is to analyze the validity and reliability of the Turkish translation of the Kiddie Schedule for Affective Disorders and Schizophrenia for School-Age Children - Mania Rating Scale (K-SADSC-MRS), and the Depression Rating Scale (K-SADSC -DRS). METHODS: 151 children and adolescents (6 - 18 years old) and 30 healthy controls (6 - 18 years old) who applied to the Child and Adolescent Psychiatry clinic between September 2020 and May 2022 were included in the study. All participants were given K-SADSC-MRS, K-SADSC-DRS, Children's Depression Rating Scale - Revised Form (CDRS), Young Mania Rating Scale (YMRS), Children's General Assessment Scale (CCI) and Clinical Global Impression Scale (CGI) ) scales were applied. RESULTS: Cronbach's alpha coefficient of K-SADSC-MRS was found to be 0.899 and similarly, Cronbach's alpha coefficient of K-SADSC-DRS was found to be 0.899. A high correlation was found between YMRS and K-SADSC-MRS (r=0.932, p< 0.001), and between CDRS and K-SADSC-DRS (r=0.911, p< 0.001). There was a negative correlation between the scales showing opposite polarity. In ROC analyses, the area under the curve was found to be 0.927 for K-SADSC-MRS and 0.920 for K-SADSC-DRS. Intra-class correlation coefficients between the interviewers were için 0,996 (%95 confidence interval= 0,992 – 0,998) for K-SADSC-MRS and 0,980 (%95 confidence interval= 0,956 – 0,991) for K-SADSC-DRS. DISCUSSION AND CONCLUSION: The Turkish forms of K-SADSC-MRS and K-SADSC-DRS are valid and reliable scales and are suitable for use in children and adolescents in our country.